Determination of Shape Coefficient in Elastic Modulus Estimation with Penetration Test - Tongbin Zhao; Rui Mao; Kai Fang; Biwen Zhang; Fenghai Yu (Advances in Civil Engineering)
Elastic modulus is a significant parameter in design and construction for rock engineering. Rock penetration test as a convenient method to evaluate the modulus of rocks has a great potential to be used. Based on the elastic theory, the relationship between rock penetration behavior and elastic modulus was established. In order to evaluate the elastic modulus, the shape coefficient is an important parameter to be determined. However, due to many factors, the value of this parameter is still uncertain. To provide a better insight into the shape coefficient and its factors, a series of penetration tests which used several types of rock samples with different sizes were conducted to study the determination of shape coefficient under different conditions. The test results show that sample size influences the shape coefficient, and with the increase in size, the shape coefficient decreases gradually to a stable value. In contrast, confining pressure has less effect on shape coefficient, and in the moderate and low stresses region, a fixed value can be selected for the test. Different types of rocks correspond to different shape coefficients. The shape coefficient of hard rock is higher than that of soft rock. Shape coefficient should be selected reasonably according to the penetration depth in practical application, and the reason, furthermore, why back-calculated shape coefficient deviates from the theoretical value is also discussed.